La CEE : Les normes réelles de la politique agricole commune - Eversley, Judith (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
The paper attempts to describe and explain developments in European Community agricultural policy in the last decade in the light of the political considerations underlying national and supra-national behaviour. Suggestions for reforms are made, but the main emphasis is on the need for the real objectives and hopes of the Community's members to be made explicit and then reconciled.